EDITORIAL: IJIEM as a part of the world’s leading scientific citation search platform - Marjanovic, Ugljesa (International Journal of Industrial Engineering and Management, 2022)
Clarivate Analytics’s Web of Science (WoS) is the leading scientific citation search platform. As of May 9, 2022, the International Journal of Industrial Engineering and Management (IJIEM) is a part of it. The IJIEM articles will be indexed in Emerging Sources Citation Index (ESCI) within the category engineering, industrial. This remarkable result is achieved with the support and contribution of readership, authors, reviewers, editorial board members, and all other stakeholders. However, ESCI is only a milestone. The final goal of the IJIEM is to receive Journal Impact Factor (JIF). On this path, the IJIEM will continue serving researchers and practitioners in production management.